FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMERIKSAAN TRIPLE ELIMINASI PADA IBU HAMIL DI PUSKESMAS - Siti Fatimah; Yessy Arisman; Lisnawati Nur Farida; Innas Tiara Ardhiani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
One of the health issues that remains a challenge in Indonesia is the high incidence of infectious diseases, particularly Human Immunodeficiency Virus (HIV)/AIDS, syphilis, and hepatitis B. The objective of this study was to identify factors associated with triple elimination screening among pregnant women at community health centers. A cross-sectional study design was used. The study was conducted in the service area of the Pagar Dewa Community Health Center. The study was conducted in April 2025. The study population consisted of all pregnant women registered at the Pagar Dewa Community Health Center. The sample comprised 60 respondents. The sampling technique used was purposive sampling. The research instrument used a questionnaire. Data analysis was performed using univariate and bivariate methods. The results indicated an association between knowledge (p-value: ) and spousal support (p-value: ) with triple elimination screening. It is recommended that pregnant women have greater access to information about the importance of triple elimination. In addition to information from health workers, pregnant women can also access information through electronic and print media. A recommendation for health workers is to conduct outreach about the triple elimination program to couples of reproductive age and women of reproductive age, both in person and through health education materials posted at the Community Health Center. Keywords: Spousal Support, HIV, Triple Elimination